Haematopoietic developmental potential of human pluripotent stem cell lines - Tesařová, L; Simara, P; Stejskal, S; Koutná, I (Folia biologica, 2014)
The generation of haematopoietic progenitors from human pluripotent stem cells (hPSCs) presents great promise for cell-replacement therapies. However, current protocols for haematopoietic differentiation of hPSCs suffer from low efficiency and functional defects in the derived cells. The technology is also limited by variable ability of hPSC lines to generate blood cells in vitro. To address this issue, methodologies for haematopoietic differentiation in feeder-free conditions were applied to available human embryonic stem cell (hESC) and human induced pluripotent stem cell (hiPSC) lines in this study. It was found that these cell lines did not generate haematopoietic progenitors to such an extent as did H1 and H9 hESC lines that were used for this purpose in the vast majority of relevant studies. These results suggest that for clinical application of blood cells derived from hPSCs, possibly from autologous hiPSCs, it is necessary to overcome the variability in the haematopoietic developmental potential of individual hPSC lines.
Keywords: Cell Differentiation; Induced Pluripotent Stem Cells; pluripotentní kmenové buňky; hematopoetické kmenové buňky; lidé; buněčná diferenciace; indukované pluripotentní kmenové buňky; Cell Line; Pluripotent Stem Cells; Humans; Hematopoietic Stem Cells; buněčné linie